PREVALENCE OF BACTERIAL VAGINAL INFECTIONS IN PRE AND POSTMENOPAUSAL WOMEN - LAKSHMI K; CHITRALEKHA S; ILLAMANI V; MENEZES GA (International Journal of Pharma and Bio Sciences, 2012)
Estrogen deficiency around menopause can cause growth of abnormal flora leading to infections. The aim of the study was to assess the prevalence of bacterial vaginal infections among the asymptomatic pre and postmenopausal women. High vaginal swab samples were collected and the microorganisms were identified. Their antibiotic susceptibility pattern was noted. Escherichia coli, Staphylococcus aureus and Candida sp. were isolated from 15.2%, 8.7%, 19.6% premenopausal women and 14.8%, 9.3%, 13% postmenopausal women respectively. Lactobacillus was found in 34.8% premenopausal and 27.8% postmenopausal women. The higher prevalence of pathogenic bacteria and relative depletion of Lactobacilli in postmenopausal women increases the risk of bacterial vulvovaginitis in them. Pathogenic bacteria were also found as frequently as Candida sp. in the pre and postmenopausal women. Hence, the practice of empirical antifungal therapy without taking high vaginal swab needs to be revised. Consideration should be given for the use of appropriate antibiotics along with antifungal drugs.